The drivers of adoption and impact of climate-smart agricultural practices on livestock farmers’ household welfare in Pakistan - Arshad, Mahwish; Abdulai, Awudu (Frontiers in Sustainable Food Systems, 2025)
Climate change remains a major challenge for farmers who rely on nature-based livelihoods such as livestock, which is a crucial aspect of income generation and food security in developing countries. In this study, we examine the determinants of livestock farmers’ adoption of climate-smart agricultural (CSA) practices and the impact of adoption on food security and household income in Punjab, Pakistan. The two CSA practices include livestock management (housing modification, livestock diversification, reducing herd size, and incorporating trees into livestock farming) and health and feed management (animal healthcare measures, feeding practices, enhanced fodder, and manure incorporation). We employ data from 428 livestock farmers in five districts of Punjab, employing a multinomial endogenous switching regression model to address potential selection bias. The results reveal that factors affecting CSA practice adoption include livestock units, landholdings, perception of climate change, climate indicators, veterinary center access, farming experience, and perception of increasing animal diseases. We also demonstrate that livestock farmers who adopt combined CSA practices benefit more than those who do not adopt any or adopt an individual practice, in terms of food security and household income. The findings also reveal that farmers’ perception of climate change and veterinary center access promote the adoption of CSA practices.